What is this thing called jazz? : African American musicians as artists, critics, and activists - Porter, Eric (Eric C.) (Music of the African diaspora, 2002)
Despite the plethora of writing about jazz, little attention has been paid to what musicians themselves wrote and said about their practice. An implicit division of labor has emerged where, for the most part, black artists invent and play music while white writers provide the commentary. Eric Porter overturns this tendency in his creative intellectual history of African American musicians. He foregrounds the often-ignored ideas of these artists, analyzing them in the context of meanings circulating around jazz, as well as in relationship to broader currents in African American thought.<b.